Influence of preoperative voice assessment on treatment plan prior to airway surgery. (12th September 2018) - Bergeron, Mathieu; Kelchner, Lisa; Weinrich, Barbara; Brehm, Susan Baker; Zacharias, Stephanie; Myer, Charles; Alarcon, Alessandro de
Abstract : Objectives/Hypothesis: Voice quality has emerged as an additional long‐term outcome measure for patients with a history of airway surgery. The goal of this study was to evaluate the impact of preoperative voice assessment on the surgical management of patients who required complex airway surgery. Study Design: Retrospective case series. Methods: We analyzed clinical data for all patients who underwent an airway reconstruction procedure from September 1, 2012 to September 1, 2017 and had a voice clinic evaluation prior to surgery at a tertiary‐care pediatric hospital. Each participant underwent a full clinical voice evaluation that yielded acoustic, imaging, perceptual, and handicapping index data. Results: Six hundred forty‐three patients underwent 831 airway surgeries (laryngotracheoplasty, cricotracheal resection, slide tracheoplasty, laryngeal cleft repair). Ninety‐one (14.2%) of the 643 patients underwent a formal voice clinic evaluation prior to airway surgery; 39/91 (42.9%) were female. The mean age was 10.4 years (95% confidence interval [CI]: 9.2‐11.6) with 31/91 (32.9%) participants demonstrating vocal fold immobility and 33/91 (36.3%) vocal fold hypomobility. A voice clinic evaluation provided new information for 62/91 (68.1%) patients, mainly for laryngeal dynamic components (vocal fold motion, source of phonation, arytenoid prolapse) and confirmed suspected disorders for the remaining patients. The average baseline Pediatric Voice Handicap Index overall score was 38.9 (95% CI: 33.3‐44.5), and the average overall severity rating of the Consensus Auditory‐Perceptual Evaluation of Voice was 54 (95% CI: 45.2‐62.8). A voice clinic evaluation influenced management of 56/91 (61.5%) patients either by modification of the surgical plan (26/56, 46%) and/or adjusting voice therapy (21/56, 37.5%). Conclusions: Voice evaluation prior to airway reconstruction provided key information that influenced the management for most of the patients. Formal voice evaluation should be considered prior to complex airway surgery. Level of Evidence: 4 Laryngoscope, 128:2858–2863, 2018